A practical roadmap for the digital transformation of urban water systems – using insights from a Swedish utility to chart the path forward - Miltell, Maya; Okwori, Emmanuel; Jennehag, Ulf; Kardeby, Victor; Arnell, Magnus (Water Practice and Technology, 2025)
Urban water systems are facing growing challenges, including climate change and aging assets. Digital transformation presents opportunities to address these issues. However, water utilities often encounter barriers such as fragmented initiatives, organizational inertia, and lack of systems interoperability, limiting the scalability and impact of digitalization efforts. This paper presents a strategic roadmap for the digital transformation of water utilities, developed through a literature review and a case study of Vakin, a water utility in Sweden. The findings highlight that organizational and cultural factors are as critical as technical solutions for successful transformation. The study presents arguments that digitalization must be driven by organizational needs and framed within a systems-thinking perspective, resembling strategic organizational development rather than isolated projects. This paper also argues that digital transformation needs to resemble strategic organizational development more than a digitalization project. The proposed approach fosters flexibility, interoperability, and a culture of prototyping and continuous improvement, providing a structured framework for utilities to navigate digital transformation and enhance sustainability.
Publisher Copyright: © 2025 The Authors.
Keywords: asset management; data management; digital culture; digitalisation; IoT; utility management